Pengaruh Kompetensi Pedagogik Terhadap Evaluasi Pembelajaran Siswa Madrasah Aliyah - Momon Andriwinata (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2023)
The background of this research is the weakening of pedagogical competence among teachers of Islamic high schools. The presence of teacher certification does not seem to be in line with the expected results. Therefore, this study aims to determine the effect of pedagogical competence on the ability to evaluate learning among madrasah aliyah teachers. This study uses an analytical descriptive method using a quantitative approach. Data processing using SPSS (test for normality, homogeneity, test, F and T-Test). The findings showed that the average quality profile of teacher pedagogic competence on learning evaluation was 82.03%, meaning that the MA Negeri 2 Serang Banten teacher mastered pedagogic competence and on average the quality profile of the ability to evaluate learning is 80.00%, meaning that teachers of MA Negeri 2 Serang Banten master learning evaluation. The effect of pedagogic competence has a significant positive effect of 0.503/50.3% on learning evaluation. The results of SPSS calculations lie in the details of the categories obtained from research. According to the calculation of the t-test, the t- count value of 3.162 is greater than the t-table of 2.042 for a significant 5% dk = 40-1 = 39. Because the t-count is greater than the t-table, Ha is accepted and Ho is rejected. The research recommendations are addressed to the head of Madrasah MA Negeri 2 Serang Banten, MA education providers, and teachers to improve the ability to evaluate learning requires good pedagogic mastery.